(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the gender characteristics of address forms in English and Uzbek languages from a comparative linguistic perspective. The study analyzes the lexical, cultural, and pragmatic features of gender-specific address units used in interpersonal communication. Particular attention is paid to the influence of social status, age, respect, and national-cultural values on the formation and use of address forms in both languages. The research highlights similarities and differences in male and female forms of address and explains their role in expressing politeness, social relationships, and communicative intentions. The article also discusses the impact of gender stereotypes and sociolinguistic factors on the development of address units in English and Uzbek speech culture. The findings demonstrate that address forms reflect not only linguistic structures but also the cultural and social norms of society.